2010
DOI: 10.1074/jbc.m110.179093
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Calmodulin to the HIV-1 Matrix Protein Triggers Myristate Exposure

Abstract: Steady progress has been made in defining both the viral and cellular determinants of retroviral assembly and release. Although it is widely accepted that targeting of the Gag polypeptide to the plasma membrane is critical for proper assembly of HIV-1, the intracellular interactions and trafficking of Gag to its assembly sites in the infected cell are poorly understood. HIV-1 Gag was shown to interact and co-localize with calmodulin (CaM), a ubiquitous and highly conserved Ca 2؉ -binding protein expressed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
59
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 92 publications
10
59
1
Order By: Relevance
“…Our recent NMR studies revealed that the majority of 1 H, 15 N resonances corresponding to residues in the N-terminal region of MA (residues ϳ2-50) exhibit significant chemical shift changes upon binding to CaM (46). However, extensive loss and/or broadening of the NMR signals precluded unambiguous identification of residues critical for binding.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our recent NMR studies revealed that the majority of 1 H, 15 N resonances corresponding to residues in the N-terminal region of MA (residues ϳ2-50) exhibit significant chemical shift changes upon binding to CaM (46). However, extensive loss and/or broadening of the NMR signals precluded unambiguous identification of residues critical for binding.…”
Section: Resultsmentioning
confidence: 99%
“…As indicated by the sign of the heat of enthalpy, CaM binding to MA-(11-28) is exothermic, suggesting that electrostatic interactions may also play a role along with the proposed hydrophobic interactions (Table 1). Of particular note, we have previously shown that CaM interactions with the full-length MA protein are mainly hydrophobic (46).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations